Gerakan Sadari Dan Sadanis Sebagai Upaya Pencegahan Kanker Payudara Untuk Meningkatkan Kesehatan Reproduksi Wanita - Metasari, Des; Rahmawati, Diyah Tepi; Syafrie, Ice Rakizah (Jurnal Dehasen Untuk Negeri, 2025)
Deaths from cervical cancer occur in low and middle income countries such as Indonesia, GLOBOCAN (2019) states that breast cancer ranks second in Indonesia as a cause of death from cancer. Public awareness to carry out early detection efforts for cancer results in many cancer patients who do not know about it and only use health services at a late stage, as a result of which maximum treatment cannot be carried out. Prevention of death can be overcome by increasing public knowledge and early detection efforts through breast self-examination (SADARI) and clinical breast examination (SADANIS)The purpose of this activity is to increase WUS knowledge and teach SADARI and SADANIS examinations.This activity was carried out from May to July 2024 in Bengkulu City on 50 WUS, by providing education about cancer to mobilizing the community to carry out SADARI independently and facilitating SADANIS activities in health service facilities that are referrals for WUS health insurance.The result is 80% of their knowledge increased, 100% were able to demonstrate SADARI according to SOP, 78% performed SADANIS in local health services with the result that no one was at risk of breast cancer. Providing education and simulation of SADARI and SADANIS activities effectively mobilizes the community to make efforts for early detection of breast cancer. The role of health workers in disseminating health information and simulations with the community directly can improve optimal health levels.